P0879EARLY STEROID WITHDRAWAL HAS A POSITIVE EFFECT ON BONE KIDNEY TRANSPLANT RECIPIENTS: A PROPENSITY SCORE STUDY WITH INVERSE PROBABILITY-OF-TREATMENT WEIGHTING. (6th June 2020) - Batteux, Benjamin; Gras-Champel, Valérie; Lando, Mathilde; Brazier, François; Desailly-Henry, Isabelle; Rey, Amayelle; Benis, Youssef; Masmoudi, Kamel; Choukroun, Gabriel; Liabeuf, Sophie
Abstract: Background and Aims: Long-term corticosteroid use after kidney transplantation is associated with a decrease in bone mineral density and a high fracture risk. We hypothesized that patients with early steroid withdrawal (ESW) would display a gain in bone mineral density in the year following kidney transplantation, when compared with patients on long-term corticosteroid therapy (LTCT). Method: In a cohort of kidney transplant recipients, 317 patients were included between 2012 and 2018. Dual-energy X-ray absorptiometry was performed 1 and 12 months after transplantation. The data were analyzed using linear regression with inverse probability‐of‐treatment weighting based on a propensity score. Results: One year after transplantation, the gain in bone mineral density was significantly greater in recipients with ESW than in recipients on LTCT for the lumbar spine (+0.027 g/cm, P < 0.001) and the femoral neck (+0.021 g/cm, P = 0.035). Among patients with ESW, (i) none had osteoporosis, (ii) the percentage with normal bone mineral density increased from 35.0% at month 1 to 56.4% at month 12, and (ii) the percentage with osteopenia fell from 52.5% to 43.6%. In patients undergoing LTCT, the fracture incidence was 14.5 per 1000 person-years. None of the patients in the ESW group experienced a fracture. Cardiovascular risk factors were more prominent in the LTCT group relative to the ESW group: patients in LTCT group (i) were more likely to have high blood pressure (p<0.001), (ii) gained more weight gain (p=0.032) and (iii) displayed a greater increase in serum triglyceride levels (p=0.004).The acute rejection rate was similar in the two groups. Conclusion: Early steroid withdrawal is associated with a spontaneous increase in bone mineral density at 12 months post-transplantation (relative to patients on long-term steroid therapy), with a reduction in several cardiovascular risk factors and does not appear to harm the graft.